Genotype-phenotype correlations of fasting C-peptide and lipids in HNF1A-MODY: a single-center series and multi-center cross-sectional analysis in Chinese population - Wang, Mengyu; Huang, Hulian; Liu, Hualin; Tian, Huihui; Hou, Xinguo; Chen, Li; Tian, Meng; Wang, Lingshu (Frontiers in Endocrinology, 2026)
BackgroundHNF1A-MODY is one of the most prevalent subtypes of maturity-onset diabetes of the young (MODY). Individuals with HNF1A-MODY display considerable clinical heterogeneity, potentially attributable to specific mutation sites. However, in the Chinese population, the relationship between distinct mutation sites and clinical manifestations remains to be investigated.MethodsIn the initial analysis, 23 HNF1A-MODY patients diagnosed at the Department of Endocrinology, Qilu Hospital were included. These patients were followed up regularly to monitor glycemic control status and the progression of complications. In the subsequent analysis, baseline information of 113 Chinese HNF1A-MODY retrieved from public databases were further enrolled. Analysis of covariance was conducted to investigate the genotype-phenotype associations.ResultsThis study included a total of 136 patients. Among the 23 from Qilu Hospital, 22 distinct HNF1A gene variants were identified, including 8 novel ones. After excluding cases classified as “variant of uncertain significance”, the analysis showed that the median age of onset was earliest in patients with DNA-binding domain mutations (15.70 years), compared to the dimerization or transactivation domain mutations (p = 0.044). Fasting C-peptide levels were markedly lower in the dimerization domain and DNA-binding domain group (p = 0.005). Patients with DNA-binding domain mutations demonstrated lower low-density lipoprotein cholesterol (p = 0.049) and total cholesterol (p = 0.016) levels, but higher high-density lipoprotein cholesterol (p = 0.036) levels. Analysis of covariance indicated that mutations in the dimerization domain (mean difference = -0.757, p = 0.001) and DNA-binding domain (mean difference = -0.331, p = 0.041) were independently associated with lower fasting C-peptide, and DNA-binding domain mutations were also associated with low-density lipoprotein cholesterol (mean difference = -0.554, p = 0.015) and higher high-density lipoprotein cholesterol (mean difference = 0.224, p = 0.015) levels, whereas the other domain mutations showed no statistically significant associations.ConclusionThis study revealed the correlation between HNF1A mutation regions and pancreatic islet function as well as blood lipids in Chinese HNF1A-MODY patients, thereby underscoring the importance of early genetic identification in formulating individualized therapeutic strategies to improve prognosis.